Preparation method of perovskite film and perovskite solar cell

By electrostatic spraying of metal halide powder and processing in organic halide steam, the problems of toxic solvents, low coverage and waste of materials in the preparation of perovskite films in the prior art are solved, and the preparation of high-quality perovskite films is achieved. and the performance of perovskite solar cells is improved.

CN119486545APending Publication Date: 2025-02-18CHANGZHOU S C EXACT EQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411584666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when preparing perovskite solar cells, the perovskite precursor solution used has toxic solvents, and the scraping method results in low coverage of the perovskite film, poor crystallization quality, and material waste. .

Method used

High-quality perovskite films were prepared by electrostatic spraying of metal halide powder and treated in a steam atmosphere of organic halides. This method does not use harmful solvents, improves the coverage and crystallization quality of the film, and saves materials through recycling of the steam chamber.

Benefits of technology

The high coverage rate of perovskite film, good crystallization quality and material savings are achieved, the production cost is reduced, and the effective area and efficiency of perovskite solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486545A_ABST
    Figure CN119486545A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite film and a perovskite solar cell. The preparation method of the perovskite film comprises the following steps: electrostatically spraying metal halide powder on a substrate to obtain a thin film, and treating the thin film in a steam atmosphere of organic halide to obtain the perovskite film. The perovskite light absorption layer in the perovskite solar cell is the perovskite film prepared by the preparation method of the perovskite film. The perovskite film is prepared by adopting a method of electrostatic powder spraying and steam treatment, so that the uniformity of the perovskite light absorption layer, the film forming quality and the coverage rate of the perovskite film on the substrate can be improved, and the effective area of the perovskite solar cell is increased. Organic halide steam is recycled, so that materials are saved, and the cost is reduced. In the preparation process of a large-area device, a uniform and high-quality perovskite film can be obtained, and commercialization of a perovskite solar cell is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a method for preparing an environmentally friendly and efficient perovskite film and a perovskite solar cell having the perovskite film. Background Art

[0002] In the process of preparing perovskite solar cells, a spin coating method is usually used to spin-coat a perovskite precursor solution to prepare a perovskite light absorption layer. Since large-area devices are the mainstream trend of the current development of perovskite solar cells, when making a large-area perovskite light absorption layer, a scraping method is often used to apply the precursor solution on a substrate. The perovskite precursor solution is mainly composed of a mixture of metal halides, organic halides and solvents. After being spin-coated into a thin film, it is heated to form a perovskite light absorption layer. Since a solvent with a certain toxicity is used, it is not conducive to environmental protection. In addition, scraping will reduce the coverage of the perovskite film on the substrate. It is difficult to form a uniform film layer when scraping over a large area, which will reduce the crystallization quality of the perovskite crystals, and a considerable amount of solution will remain on the edge of the substrate or be taken away by the scraper, causing unnecessary waste.

[0003] Therefore, how to overcome the defects of the prior art in producing perovskite solar cells, such as the use of environmentally unfriendly solvents in the perovskite precursor solution for preparing the perovskite light absorption layer, the low crystallization quality of the perovskite crystals, and the waste of materials, is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] The present invention provides an environmentally friendly and efficient method for preparing a perovskite film and a perovskite solar cell in order to solve the technical problems that the perovskite precursor solution used in the prior art for preparing a perovskite light absorption layer uses a solvent that is not environmentally friendly, the crystallization quality of the perovskite crystal is not high, and materials are wasted. The perovskite film prepared by the present invention has high crystallization quality of the perovskite crystal, saves waste, and reduces costs.

[0005] The present invention provides a method for preparing a perovskite film, comprising the following steps:

[0006] The metal halide powder is electrostatically sprayed on the substrate to obtain a thin film, and then the thin film is placed in an organic halide vapor atmosphere for treatment to obtain the perovskite film.

[0007] Preferably, the film is placed in a steam chamber, the organic halide vapor enters from a hot end inlet of the steam chamber and exits from a cold end outlet, and the output organic halide vapor is recycled and reused through a circulation device;

[0008] Preferably, the film is placed in a steam chamber pre-filled with the organic halide vapor, and the film is treated to obtain a perovskite film, and the organic halide vapor is recovered and reused through a circulation device.

[0009] Preferably, the metal halide is lead iodide PbI 2 、Lead chloride PbCl 2 、Lead bromide PbBr 2 , Cesium iodide CsI 2 , Cesium bromide CsBr 2 , Cesium chloride CsCl 2 , Tin Iodide SnI 2 , Tin Bromide SnBr 2 or tin chloride SnCl 2 At least one of .

[0010] Preferably, the organic halide is at least one of methylamine iodide FAI, methylamine iodide MAI, methylamine chloride FACl, methylamine chloride MACl, methylamine bromide FABr or methylamine bromide MABr.

[0011] Preferably, the distance between the electrostatic spraying nozzle and the substrate is 1-50 cm; the voltage of the electrostatic spraying is 20-100 kV; and the electrostatic spraying time is 10-60 seconds.

[0012] Preferably, the steam chamber is processed under normal pressure or vacuum.

[0013] Preferably, the organic halide vapor flows through the steam chamber at a rate of 500-2000 mL / min for a duration of 10-30 min.

[0014] The present invention also provides a perovskite solar cell, characterized in that it comprises a perovskite light absorbing layer, and the perovskite light absorbing layer is a perovskite film prepared by the method of the present invention.

[0015] Preferably, the perovskite solar cell includes a formal single-junction perovskite solar cell, an inverted single-junction perovskite solar cell, a perovskite / perovskite tandem solar cell, a perovskite / crystalline silicon tandem solar cell or a perovskite / copper indium gallium tin CIGS tandem solar cell.

[0016] The present invention adopts the method of "electrostatic spraying powder + steam treatment" to prepare the perovskite film, and the steam chamber structure of the present invention includes but is not limited to tubular type, box type, etc. That is, the first step is electrostatic spraying of metal halide powder to obtain a film; the second step is steam treatment, that is, the film is placed in an organic halide vapor atmosphere for treatment to obtain the perovskite film. In the second step, no electrostatic spraying is used, and no separate heating is required. In this way, the uniformity of the perovskite light absorption layer, the film quality and the coverage of the perovskite film on the substrate can be improved, and the effective area of ​​the perovskite solar cell can be increased. No solvent is used, materials are saved, and organic solvent pollution is reduced. The recycling of organic halide vapor saves materials and reduces costs. In addition, the above preparation method can also be used for large-area devices. In the preparation process of large-area devices, a uniform and high-quality perovskite film is obtained, which is conducive to the commercialization of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the formal perovskite solar cell structure;

[0018] Figure 2 It is a schematic diagram of the structure of an inverted perovskite solar cell;

[0019] Figure 3 It is a schematic diagram of the structure and working principle of the tubular steam chamber;

[0020] Figure 4 is the current density and voltage JV characteristic curve of the perovskite solar cell;

[0021] Figure 5 is the external quantum efficiency EQE curve of perovskite solar cells, Figure 5 The medium current density value is the integrated current density of the battery's external quantum efficiency;

[0022] Figure 6 This is the SEM image of the perovskite film prepared in Comparative Example 1 (magnification 10000 times);

[0023] Figure 7 This is the SEM image of the perovskite film prepared in Example 1 (magnification 10,000 times). DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the embodiments and drawings.

[0025] The present invention provides a method for preparing a perovskite film, comprising the following steps:

[0026] Step 1, electrostatically spraying metal halide powder on a substrate to obtain a thin film;

[0027] Among them, the metal halide used is lead iodide PbI 2、Lead chloride PbCl 2 、Lead bromide PbBr 2 , Cesium iodide CsI 2 , Cesium bromide CsBr 2 , Cesium chloride CsCl 2 , Tin Iodide SnI 2 , Tin Bromide SnBr 2 or tin chloride SnCl 2 At least one of .

[0028] During electrostatic spraying, only one metal halide precursor material can be sprayed, or multiple metal halide precursor materials can be mixed and sprayed together. Different metal halides are used according to the perovskite film to be prepared, such as:

[0029] (1) Precursor material spraying

[0030] Preparation of FAPbI 3 Perovskite film, electrostatic spraying PbI 2 ; Preparation of MA 0.1 FA 0.9 PbI 3 Perovskite film, electrostatic spraying PbI 2 Preparation of FASnI 3 For perovskite film, SnI is electrostatically sprayed in proportion. 2 Preparation of FAPbBr 3 Perovskite film, electrostatic spraying PbBr 2 ;

[0031] (2) Multiple precursor materials are mixed and sprayed together

[0032] Preparation of FASnI 0.95 Br 0.05 For perovskite film, SnI is electrostatically sprayed in proportion. 2 and SnBr 2 Preparation of Cs 0.05 FA 0.95 PbI 3 For perovskite film, PbI is electrostatically sprayed in proportion. 2 and CsI 2 ; Preparation of FA PbI 0.9 Br 0.05 Cl 0.05 For perovskite film, PbI is electrostatically sprayed in proportion. 2 、PbBr 2 and PbCl 2 , that is, the three materials are mixed and sprayed together. Preparation of Cs 0.05 FA 0.85 MA 0.1 PbI 3For perovskite film, PbI is electrostatically sprayed in proportion. 2 and CsI 2 .

[0033] The distance from the nozzle of electrostatic spraying to the substrate can be 1-50 cm. As needed, the distance can be selected, for example, 1 cm, 5 cm, 10 cm, 15 cm, 20 cm, 25 cm, 30 cm, 35 cm, 40 cm, 45 cm, 50 cm.

[0034] When preparing batteries with smaller areas, a shorter distance is generally selected for spraying, covering a small area of ​​the substrate within a smaller range; when preparing batteries with larger areas, a longer distance is selected. The longer distance spraying can cover a larger area, and the distance can be adjusted adaptively according to the size of the battery. Selecting a distance parameter increment of 5cm facilitates adjusting the spraying distance in a small range to adapt to batteries of different sizes. At the same time, the height can be adjusted in combination with the amount of raw materials used to ensure the coverage of the perovskite raw materials on the battery substrate.

[0035] The voltage of electrostatic spraying can be 20-100 kV. As needed, the voltage can be selected, for example, 20 kV, 30 kV, 40 kV, 50 kV, 60 kV, 70 kV, 80 kV, 90 kV or 100 kV.

[0036] When the voltage increases, the electric field force of the electrostatic field will be strengthened, which is conducive to the rapid adhesion of raw materials to the substrate surface and increases the utilization rate of raw materials; but the voltage should not be too large, otherwise it will easily generate spark power generation; so the voltage can be adjusted according to the amount of raw materials used.

[0037] The electrostatic spraying time is 10-60 seconds. The time can be selected as needed, for example, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds or 60 seconds.

[0038] If the spraying time is long, the amount of raw materials sprayed will increase, which can increase the thickness of the film; if the spraying time is short, less raw materials will be sprayed and the thickness will be thin. Optimize the time according to the amount of raw materials used and the required thickness.

[0039] Step 2: treating the film in a vapor atmosphere of an organic halide to obtain the perovskite film.

[0040] The film obtained by electrostatically spraying the metal halide powder in step 1 is placed in a steam chamber, such as a tubular steam chamber, and the organic halide vapor is transported from the hot end inlet of the tubular steam chamber to the cold end outlet. That is, the organic halide vapor is continuously transported from one end of the tubular steam chamber to the other end. At this time, the inlet and outlet of the tubular steam chamber are in an open state, and the organic halide vapor flow slowly flows while fully reacting with the metal halide film to obtain the perovskite film of the present invention. Since the organic halide vapor in the tubular steam chamber moves in the same direction, the vapor flowing out of the outlet end can be recycled and reused by a circulation device to save materials.

[0041] The film can also be processed under the state that the steam of organic halide does not flow. That is, the steam of organic halide is pre-filled in the tubular steam chamber, and the organic halide steam flows into the steam chamber inside through the hot end inlet heating, forming the steam atmosphere of organic halide, and then the film obtained by electrostatic spraying metal halide powder in step 1 is placed in the tubular steam chamber, at this time, the import and export of the tubular steam chamber are closed, so that organic halide and metal halide film fully react, and perovskite film is obtained. After the reaction is completed, the import and export of the tubular steam chamber are opened, and the steam in the tubular steam chamber is purged and flows out from the outlet to enter the circulation device for recycling, to save materials. Wherein, the organic halide can be at least one of methyl amidate iodine FAI, methylamine iodine MAI, methyl amidate chlorine FACl, methylamine chlorine MACl, methyl amidate bromine FABr or methylamine bromine MABr.

[0042] The tubular steam chamber is in a normal pressure or vacuum state. When the film is treated in a vacuum state, the vacuum degree is 1×10 -6 ~1×10 -2 Pa.

[0043] When preparing the perovskite film, the electrostatic spraying of metal halide powder and the treatment of organic halide steam are carried out in two separate steps. After electrostatic spraying of metal halide powder, the perovskite film cannot be obtained. Only after the second step of the organic halide steam reacts the sprayed film, it gradually grows to form complete crystals, and the perovskite film is obtained. During the reaction of the metal halide film and the organic halide steam, no separate heating is required. In this way, the uniformity of the perovskite light absorption layer, the film quality and the coverage of the perovskite film on the substrate can be improved, and the effective area of ​​the perovskite solar cell can be increased. In addition, the process is simple, there is no solvent and no pollution, and the cost is saved.

[0044] The present invention also provides a perovskite solar cell, which comprises a perovskite light-absorbing layer, and the perovskite light-absorbing layer is a perovskite film prepared by the method of the present invention.

[0045] The perovskite solar cells include formal single-junction perovskite solar cells, inverted single-junction perovskite solar cells, perovskite / perovskite tandem solar cells, perovskite / crystalline silicon tandem solar cells or perovskite / copper indium gallium tin CIGS tandem solar cells. In other words, the perovskite film (perovskite light-absorbing layer) obtained by the above preparation method can be used for the above different types of perovskite solar cells.

[0046] The steam chamber structure of the present invention includes but is not limited to a tube type, a box type, etc.

[0047] like Figure 1 As shown, the preparation method of the formal (nip) structure perovskite solar cell is as follows:

[0048] The conductive substrate is sequentially cleaned by ultrasonic cleaning with detergent, deionized water and acetone, dried in an oven and then treated under ultraviolet ozone for 30 minutes. The conductive substrate includes any one of indium tin oxide ITO glass, fluorine-doped tin oxide FTO glass and a flexible substrate.

[0049] The electron transport layer 100 is prepared on the conductive substrate after ultraviolet ozone treatment. The thickness of the electron transport layer is generally in the range of 20-500 nm. The raw materials for preparing the electron transport layer 100 include tin oxide SnO 2 , zinc oxide ZnO, aluminum oxide Al 2 O 3 , titanium dioxide TiO 2 , one or more of indene-C60 bisadduct ICBA.

[0050] Electrostatically spray metal halide powder on the conductive substrate / electron transport layer 100 to obtain a metal halide film with a thickness of generally 100-500nm. In the field of perovskite batteries, the amount of material used is generally calculated in moles. That is, the mole number is determined, and the amount of metal halide and organic halide used is calculated in combination with the stoichiometric ratio of the perovskite. After the size of the battery substrate area is determined, the mole number is obtained, and then based on the mole number and the stoichiometric ratio, the metal halide required to prepare the target perovskite can be calculated. The present invention is expressed in moles / unit area, that is, the range of moles / unit area is 0.04-0.08mmol / cm 2 .

[0051] The metal halide material can be lead iodide PbI 2 、Lead chloride PbCl 2 、Lead bromide PbBr 2 , Cesium iodide CsI 2 , Cesium bromide CsBr 2 , Cesium chloride CsCl 2 , Tin Iodide SnI 2 , Tin Bromide SnBr2 or tin chloride SnCl 2 One or more of .

[0052] The distance between the nozzle of the electrostatic spraying and the substrate is 1-50 cm, the spraying voltage is 20-100 kV, and the spraying time is 10-60 seconds.

[0053] Please combine Figure 3 As shown, organic halide powder is placed at the inlet of the tubular steam chamber in advance, the conductive substrate / electron transport layer 100 / metal halide film is placed in the tubular steam chamber, the heat source at the inlet of the tubular steam chamber is started, and the organic halide powder is heated and evaporated, the heating temperature is 100-150°C, and steam is formed. Steam is passed into the tubular steam chamber from the inlet, and reacts with the electrostatically sprayed metal halide powder film to obtain a perovskite film with a thickness of 300-1000nm. The steam air flow rate is 500-2000mL / min, and the duration is 10-30min. A small amount of unreacted organic halide flows out from the outlet with the air flow, is recovered by the circulation device, and enters the inlet of the tubular cavity again for recycling.

[0054] The metal halide film can also be treated when the organic halide steam is not flowing. That is, the tubular steam chamber is pre-filled with organic halide steam, and the organic halide steam is heated at the hot end inlet and flows into the steam chamber to form an organic halide steam atmosphere. The heating temperature is 100-150°C, and then the conductive substrate / electron transport layer 100 / metal halide film is placed in the tubular steam chamber. At this time, the inlet and outlet of the tubular steam chamber are closed, so that the organic halide and the metal halide film are fully reacted to obtain a perovskite film with a thickness of 300-1000nm. After the reaction is completed, the inlet and outlet of the tubular steam chamber are opened, and a small amount of unreacted organic halide steam in the steam chamber is purged and flows out from the outlet into the circulation device for recycling and reuse to save materials.

[0055] The organic halide material can be one or more of methylamine iodine FAI, methylamine iodine MAI, methylamine chlorine FACl, methylamine chlorine MACl, methylamine bromine FABr or methylamine bromine MABr. The powder dosage of the organic halide is adjusted in proportion according to the size of the prepared perovskite film, and generally those skilled in the art obtain it according to multiple test optimization. The steam gas flow rate is 500-2000mL / min, and the duration is 10-30min.

[0056] Then, a hole transport layer 101 is prepared on the perovskite film substrate, and the thickness of the hole transport layer is 20-200 nm.

[0057] The raw materials for preparing the hole transport layer 101 include: one or more of 2,2",7,7"-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMe TAD), polytriarylamine (PTAA), nickel oxide (NiOx), polyethylenedioxythiophene-polystyrene sulfonate (PEDOT:PSS) and cuprous thiocyanate (CuSCN).

[0058] Finally, 100 nm silver or gold was vacuum-deposited on the hole transport layer 101 as an electrode with a vacuum degree of 5×10 -4 , to obtain the formal (nip) structure perovskite solar cell.

[0059] like Figure 2 As shown, the preparation method of the inverted structure (pin) perovskite solar cell is as follows:

[0060] The conductive substrate is sequentially cleaned with detergent, deionized water, and acetone ultrasonically, dried in an oven, and then treated under ultraviolet ozone for 30 minutes. The conductive substrate is selected from any one of ITO glass, FTO glass, and a flexible substrate.

[0061] A hole transport layer 200 is prepared on the conductive substrate after ultraviolet ozone treatment, and the thickness of the hole transport layer is 3-200 nm.

[0062] The hole transport layer raw materials include: one or more of polytriarylamine (PTAA), nickel oxide (NiOx), polyethylene dioxythiophene-polystyrene sulfonate (PEDOT:PSS), cuprous thiocyanate (CuSCN) and self-assembled molecular SAM. Among them, the self-assembled single molecule SAM includes [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), 2-[(2-chlorophenyl)(phenyl)amino]ethyl benzoate (2PACz) or [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz).

[0063] Electrostatically spray metal halide powder on the conductive substrate / hole transport layer 200 to obtain a thin film. The thickness of the film is 100-500 nm. The amount of metal halide used can be calculated based on the size of the battery area, from the range of 0.04-0.08 mmol / cm2 of mole / unit area.

[0064] The distance between the nozzle of the electrostatic spraying and the substrate is 1-50 cm, the spraying voltage is 20-100 kV, and the spraying time is 10-60 seconds. The metal halide material can be any one or more of lead iodide PbI2, lead chloride PbCl2, lead bromide PbBr2, cesium iodide CsI2, cesium bromide CsBr2, cesium chloride CsCl2, tin iodide SnI2, tin bromide SnBr2 and tin chloride SnCl2.

[0065] Please combine Figure 3 As shown, the conductive substrate / electron transport layer 100 / metal halide film is placed in a tubular steam chamber. At the same time, the organic halide powder is placed at the inlet of the tubular steam chamber in advance, and the heat source at the inlet of the tubular steam chamber is started. The organic halide powder is heated and evaporated, and the heating temperature is 100-150°C to form steam. Steam is passed into the cavity from the inlet and reacts with the film obtained by electrostatic spraying to obtain a perovskite film with a thickness of 300-1000nm. The steam air flow rate is 500-2000mL / min, and the duration is 10-30min. A small amount of unreacted organic halide flows out from the outlet with the air flow, is recovered by the circulation device, and enters the inlet of the tubular cavity again for recycling.

[0066] The metal halide film can also be treated when the organic halide steam is not flowing. That is, the tubular steam chamber is pre-filled with organic halide steam, and the organic halide steam is heated at the hot end inlet and flows into the steam chamber to form an organic halide steam atmosphere. The heating temperature is 100-150°C, and then the conductive substrate / electron transport layer 100 / metal halide film is placed in the tubular steam chamber. At this time, the inlet and outlet of the tubular steam chamber are closed, so that the organic halide and the metal halide film are fully reacted to obtain a perovskite film with a thickness of 300-1000nm. After the reaction is completed, the inlet and outlet of the tubular steam chamber are opened, and a small amount of unreacted organic halide steam in the steam chamber is purged and flows out from the outlet into the circulation device for recycling and reuse to save materials.

[0067] The organic halide can be any one or more of methylamine iodide FAI, methylamine iodide MAI, methylamine chlorine FACl, methylamine chlorine MACl, methylamine bromide FABr and methylamine bromide MABr. The amount of the organic halide powder is adjusted in proportion to the size of the prepared perovskite film, and is generally optimized by those skilled in the art based on multiple tests.

[0068] Then, an electron transport layer 201 is prepared on the perovskite film. The thickness of the electron transport layer is generally 20-100 nm.

[0069] The electron transport layer material includes one or more of C60, [6,6]-phenyl-C61-butyric acid isomethyl ester (PC60BM), [6,6]-phenyl-C71-butyric acid isomethyl ester (PC70BM), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), and lithium fluoride (LiF).

[0070] Finally, 100 nm of silver or gold is vacuum-evaporated on the electron transport layer 201 as the electrode, with a vacuum degree of 5×10-4, to obtain the inverted structure (p-i-n) perovskite solar cell.

[0071] The following are the examples of preparing perovskite solar cells according to the present invention and the comparative examples of the prior art.

[0072] Example 1

[0073] As Figure 1 shown, the preparation method of the normal (n-i-p) structure perovskite solar cell is as follows:

[0074] The ITO glass is ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, with each ultrasonic cleaning time being 15 minutes, and treated with ultraviolet ozone for 20 min.

[0075] 30 nm thick SnO 2 is coated on the ITO glass as the electron transport layer 100. And it is heated at 150 °C for 30 min. Before coating, the SnO 2 solution needs to be diluted in water (volume ratio VSnO 2 :VH2O = 1:4). After cooling to room temperature, the glass / ITO / SnO 2 substrate is transferred to the base of the electrostatic powder spraying equipment for electrostatic spraying operation.

[0076] Taking the target perovskite FAxCs1-xPbI 3 (0 < x < 1) as an example, according to the molar number per unit area of 0.05 mmol / cm 2 , and an area of 100 cm 2 calculation, according to the stoichiometric ratio of PbI 2 and CsI of 1:0.05, the dosages of the metal halide PbI 2 and CsI powders are 2305 mg and 65 mg respectively; then according to the experimental optimization, the dosages of the organic halides FAI and MACl powders are 286 mg and 46 mg.

[0077] On the glass / ITO / SnO 2 substrate, PbI 2and CsI powder to obtain a metal halide film. The average thickness of the film is 300 nm. The distance between the nozzle of the electrostatic spraying and the substrate is 20 cm, the spraying voltage is 70 kV, and the spraying time is 30 seconds.

[0078] Please attach Figure 3 As shown, the glass ITO / SnO 2 / PbI 2 The film of PbI and CsI was placed in the tubular steam chamber. At the same time, 286 mg FAI and 46 mg MACl powder prepared in advance were placed at the inlet of the tubular steam chamber. The heat source at the inlet of the tubular steam chamber was started, and the powder was heated and evaporated. The heating temperature was 120-150 ° C. FAI and MACl vapors were introduced into the tubular steam chamber from the inlet and electrostatically sprayed PbI 2 React with CsI film to obtain perovskite film. The steam flow rate is 500-2000mL / min and the duration is 10-30min. 2 The amounts of CsI, FAI and MACl powders are adjusted proportionally according to the area of ​​the prepared perovskite film substrate.

[0079] Since MACl is used to regulate the nucleation and crystallization of perovskite, the content of MACl in the final perovskite film is negligible, so the above expression does not contain MACl, and the average thickness of the perovskite film is 800nm. A small amount of unreacted FAI flows out from the outlet with the air flow, is recovered by the circulation device, and enters the inlet of the tubular cavity for recycling again.

[0080] Then the glass / ITO / SnO 2 / The perovskite substrate was transferred into a nitrogen glove box and coated with Spiro-OMeTAD solution as a hole transport layer 101 with a thickness of 100 nm.

[0081] Finally, 100 nm of gold or silver was evaporated in a vacuum chamber as an electrode to produce the formal (nip) structure perovskite solar cell.

[0082] Example 2

[0083] like Figure 1 As shown, another method for preparing a perovskite solar cell with a formal (nip) structure is as follows:

[0084] The difference between Example 2 and Example 1 lies in the process of tubular steam treatment, and the rest of the preparation methods are the same.

[0085] Embodiment 2 The process of tubular steam treatment is as follows:

[0086] Prepared glass / ITO / SnO 2 / PbI 2After the films of [substances not specified] and CsI, the metal halide film is treated in a state where the vapor of the organic halide does not flow. That is, the tubular vapor chamber is pre-filled with the vapor of FAI and MACl, and powders of 286 mg of FAI and 46 mg of MACl are pre-placed at the hot-end inlet. The vapor flows into the interior of the vapor chamber after being heated at the hot-end inlet, forming an atmosphere of the organic halide vapor. The heating temperature is 120 - 150 °C, and then the glass / ITO / SnO 2 / PbI 2 and CsI films are placed in the tubular vapor chamber. At this time, the inlet and outlet of the tubular vapor chamber are in a closed state so that the organic halide and the metal halide film react fully to obtain a perovskite film with a thickness of 300 - 1000 nm. After the reaction is completed, the inlet and outlet of the tubular vapor chamber are opened, and a small amount of unreacted organic halide vapor in the vapor chamber is purged and flows out from the outlet into the recycling device for recycling to save materials.

[0087] Example 3

[0088] As Figure 2 shown, the preparation method of the inverted structure (p-i-n) perovskite solar cell is as follows:

[0089] The FTO glass is ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, and the ultrasonic cleaning time for each step is 15 minutes, and it is treated under ultraviolet ozone for 30 min.

[0090] A self-assembled monolayer SAM layer 200 with a thickness of 3 - 10 nm is coated on the FTO glass, which is the hole transport layer. Among them, SAM uses Me-4PACz. 1 mg of Me-4PACz is dissolved in 1 mL of ethanol, and then heated at 100 °C for 20 min. After cooling to room temperature, the glass / FTO / SAM substrate is transferred to the base of the electrostatic powder spraying equipment for electrostatic spraying operation.

[0091] Taking the target perovskite FA1-x-yMAxCsyPbI 3 -zBrz (0 < x < 1, 0 < y < 1, 1 > x + y > 0, 0 < z < 3) as an example, according to the molar number per unit area of 0.05 mmol / cm 2 , and an area of 100 cm 2 calculation, according to the stoichiometric ratio of PbI 2 and CsI of 1:0.05, the dosages of the metal halide PbI 2 , CsI powders are 2305 mg and 65 mg respectively; and then according to experimental optimization, the dosages of the organic halide powders FAI, MACl, and MABr are 321 mg, 18 mg, and 11 mg respectively.

[0092] Electrostatic spraying of PbI on glass / FTO / SAM substrate 2 and CsI powder to obtain a metal halide film. The average thickness of the film is 300 nm. The distance between the nozzle of the electrostatic spraying and the substrate is 20 cm, the spraying voltage is 70 kV, and the spraying time is 30 seconds.

[0093] Please combine Figure 3 As shown, the heat source at the inlet end of the tubular steam chamber is started, and 321 mg FAI, 18 mg MACl and 11 mg MABr powders prepared in advance are placed at the inlet end of the tubular steam chamber for heating and evaporation. The heating temperature is 120-150°C, and the organic halide vapor is introduced from the inlet end into the starting tubular steam chamber to react with the electrostatically sprayed metal halide film to obtain a perovskite film.

[0094] Since MACl is used to regulate the nucleation and crystallization of perovskite, the content of MACl in the final perovskite film is negligible, so the above expression does not contain MACl, and the average thickness of the perovskite film is 800nm. A small amount of unreacted FAI flows out from the outlet with the air flow and is recycled and reused through a circulation device. The steam air flow rate is 500-2000mL / min, and the duration is 10-30min. The amount of PbI2, CsI, FAI, MACl and MABr powder is adjusted in proportion to the size of the substrate area of ​​the prepared perovskite film.

[0095] The glass / FTO / SAM / perovskite substrate is then transferred into a vacuum chamber, and 50 nm thick C60 and 10 nm thick BCP are evaporated as the electron transport layer 201 .

[0096] Finally, 100 nm of gold or silver is evaporated on the electron transport layer 201 as an electrode to obtain the inverted structure (pin) perovskite solar cell.

[0097] Example 4

[0098] like Figure 1 As shown, another method for preparing a trans (pin) structured perovskite solar cell is as follows:

[0099] The difference between Example 4 and Example 3 lies in the process of tubular steam treatment, and the rest of the preparation methods are the same.

[0100] The process of tubular steam treatment in Example 3 is as follows:

[0101] Prepared glass / FTO / SAM / PbI 2After the film of glass / FTO / SAM / PbI is formed, the metal halide film is treated in a state where the steam of the organic halide does not flow. That is, the tubular steam chamber is pre-filled with the steam of FAI, MACl and MABr, and 321 mg FAI, 18 mg MACl and 11 mg MABr powder are pre-placed at the hot end inlet. The steam is heated at the hot end inlet and flows into the steam chamber to form an organic halide steam atmosphere. The heating temperature is 120-150°C. Then the glass / FTO / SAM / PbI 2 The film of CsI is placed in a tubular steam chamber. At this time, the inlet and outlet of the tubular steam chamber are closed to allow the organic halide and metal halide films to fully react to obtain a perovskite film with a thickness of 300-1000nm. After the reaction is completed, the inlet and outlet of the tubular steam chamber are opened, and a small amount of unreacted organic halide vapor in the steam chamber is purged and flows out from the outlet into a circulation device for recycling and reuse to save materials.

[0102] Comparative Example 1

[0103] The method for preparing a formal structure of a perovskite solar cell using a solution method is as follows:

[0104] The ITO glass was ultrasonically cleaned with detergent, deionized water, acetone and isopropanol, with each step lasting 15 minutes, and treated under UV ozone for 20 minutes.

[0105] Coat 30nm thick SnO on ITO glass 2 Electron transport layer, and heated at 150 ° C for 30 min. Before coating, SnO 2 The solution needs to be diluted in water (volume ratio VSnO2:VH2O = 1:4). After cooling to room temperature, the glass / ITO / SnO 2 The substrate was transferred into a nitrogen glove box.

[0106] The metal halide solution consisted of 1.4 M PbI 2 The organic halide solution was prepared by dissolving 80 mg FAI and 13 mg MACl in 1 mL isopropanol. The solution must be stirred overnight before use.

[0107] When preparing the perovskite film, 40 μL of the metal halide solution was spin-coated on the electron transport layer at 1500 rpm for 40 s; then 50 μL of the organic halide solution was spin-coated on the PbI at 1800 rpm. 2 / CsI liquid film, the rotation time is 40s. Then, it is pre-annealed at 90℃ in the glove box for 1min, and then heated at 150℃ in the air outside the glove box for 10min, and the air humidity is controlled at 30% to 40%. The perovskite film FAxCs1-xPbI3(0 <x<1)。

[0108] The glass / ITO / SnO2 / perovskite substrate was transferred into a nitrogen glove box and coated with Spiro-OMeTAD solution as a hole transport layer with a thickness of 100 nm.

[0109] Finally, 100nm of gold or silver was evaporated in a vacuum chamber as an electrode to produce a perovskite solar cell with a formal structure of conventional technology.

[0110] Comparative Example 2

[0111] The method for preparing a trans-structured perovskite solar cell using a solution method is as follows:

[0112] The FTO glass was ultrasonically cleaned with detergent, deionized water, acetone and isopropanol, with each step lasting 15 minutes, and treated under UV ozone for 30 minutes.

[0113] A 3-10 nm thick self-assembled monomolecular SAM layer was coated on the FTO glass, which was the hole transport layer. Me-4PACz was used as the SAM. 1 mg of Me-4PACz was dissolved in 1 mL of ethanol and then heated at 100 °C for 20 min. After cooling to room temperature, the glass / FTO / SAM substrate was transferred to a nitrogen glove box.

[0114] The metal halide solution consisted of 1.4 M PbI 2 The organic halide solution was prepared by dissolving 90 mg FAI, 5 mg MACl and 3 mg MABr in 1 mL isopropanol. The solution must be stirred overnight before use.

[0115] When preparing the perovskite layer, 40 μL of the metal halide solution was spin-coated on the substrate at 1500 rpm for 40 seconds; then 50 μL of the organic halide solution was spin-coated on the PbI substrate at 1800 rpm. 2 / CsI liquid film, the rotation time is 40s. Then, it is pre-annealed at 90℃ in the glove box for 1min, and then heated at 150℃ in the air outside the glove box for 10min, and the air humidity is controlled at 30% to 40%. The 800nm ​​thick perovskite film FA1-x-yMAxCsyPbI 3-zBrz(0 <x<1,0<y<1,1> x+y>0,0 <z<3)。

[0116] The glass / FTO / SAM / perovskite substrate was transferred to a vacuum chamber, and 50nm thick C60 and 10nm thick BCP were evaporated as electron transport layers. Finally, 100nm of gold or silver was evaporated as electrodes to produce a conventional inverse structure perovskite solar cell.

[0117] The samples of the above four embodiments and two comparative examples are tested and compared as follows:

[0118] Testing tools and testing methods: The efficiency of perovskite solar cells is measured using a Keithley 2400 source meter under the AM1.5G solar spectrum, and the JV characteristic curve of the photovoltaic cell is obtained using an Oriel 9600 solar simulator ( Figure 4 The external quantum efficiency (EQE) was measured using an integrated system (Enlitech) with a lock-in amplifier and a current preamplifier under short-circuit conditions.

[0119] Measured parameters:

[0120] Cell efficiency; JV characteristics of photovoltaic cells; external quantum efficiency (EQE)

[0121] The characteristic curve of external quantum efficiency EQE is as follows Figure 5 As shown, the percentage is the external quantum efficiency. Figure 5 (The abscissa is wavelength, the ordinate is EQE) The data shown represent the integrated current.

[0122] The measurement results are shown in Table 1:

[0123] Table 1

[0124]

[0125] When measuring battery efficiency, the instrument can also give the short-circuit current density; the open-circuit voltage is Figure 4 The middle curve is the value when the current is 0, and the short-circuit current is the value when the voltage is 0. The fill factor is based on Figure 4 The curve test computer automatically calculates it. The fill factor refers to the ratio of the maximum power of the solar cell to the product of the open circuit voltage and the short circuit current. The larger the fill factor, the higher the quality of the solar cell.

[0126] Figure 6 and Figure 7 The scanning electron microscope images of the thin films were recorded using a field emission scanning electron microscope (SEM) for the samples of Comparative Example 1 and Example 1, respectively. Figure 6 and Figure 7By comparison, it can be seen that the surface of the perovskite film prepared by the existing solution processing technology presents many defects, the gaps at the crystal grain boundaries are wide, and no dense crystal structure is formed, which leads to easy recombination of holes and electrons at the defects, shortening the carrier lifetime, reducing the short-circuit current and filling factor, and thus reducing the battery photoelectric conversion efficiency. In the perovskite film prepared by the method of the present invention, the crystal surface defects are reduced, and there is almost no gap between the grain boundaries, resulting in a denser crystal, which can effectively improve the transmission of carriers and improve the battery photoelectric conversion efficiency.

[0127] Since the prior art uses a spin coating method to prepare a perovskite film, according to experimental statistics, the perovskite film is prepared on 20 conductive substrates under the same steps, and the coverage area of ​​the perovskite film on the conductive substrate / the area of ​​the conductive substrate is used to obtain an average coverage rate of 88%. The method of the present invention is used to prepare a perovskite film, and the perovskite film is prepared on 20 conductive substrates under the same steps. The coverage area of ​​the perovskite film on the conductive substrate / the area of ​​the conductive substrate is used to obtain an average coverage rate of 98%. That is, the uniformity of the perovskite light absorption layer, the film quality and the coverage rate of the perovskite film on the substrate are significantly improved, and the effective area of ​​the perovskite solar cell is increased.

[0128] In addition, compared with solar cells that use only an electrostatic spraying method to prepare perovskite films, the perovskite solar cells obtained using the preparation method of the present application have higher short-circuit current density and fill factor, which ultimately improves the cell efficiency. This shows that the preparation method used obtains an excellent perovskite film layer, reduces defects, and reduces the recombination of electrons and holes, so that holes and electrons are effectively transmitted to the electrode side during transmission, extending the life of holes and electrons, and obtaining a high short-circuit current and fill factor, thereby improving cell efficiency.

[0129] Due to the use of a steam chamber structure, which includes but is not limited to a tube type, a box type, etc., a perovskite film is obtained by processing under a steam process, and the organic halide vapor can be recycled and reused, saving materials and reducing costs. In addition, the above preparation method can also be used for large-area devices. In the preparation process of large-area devices, a uniform and high-quality perovskite film is obtained, which is conducive to the commercialization of perovskite solar cells.

[0130] The present invention combines electrostatic powder spraying and steam treatment to prepare the perovskite light-absorbing layer, does not use solvents, saves materials, and reduces pollution of organic solvents.

[0131] The above description is only a specific implementation of the present invention. It should be pointed out that any modification, equivalent substitution and change made within the spirit and framework of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a perovskite film, comprising the following steps: The metal halide powder is electrostatically sprayed on the substrate to obtain a thin film, and then the thin film is placed in an organic halide vapor atmosphere for treatment to obtain the perovskite film.

2. The method for preparing a perovskite film according to claim 1, characterized in that: The film is placed in a steam chamber, and the organic halide steam enters from a hot end inlet of the steam chamber and exits from a cold end outlet. The output organic halide steam is recovered and reused through a circulation device.

3. The method for preparing a perovskite film according to claim 1, characterized in that: The film is placed in a steam chamber pre-filled with the organic halide vapor, and the film is treated to obtain a perovskite film. The organic halide vapor is recycled and reused through a circulation device.

4. The method for preparing a perovskite film according to claim 1, wherein: The metal halide is at least one of lead iodide PbI2, lead chloride PbCl2, lead bromide PbBr2, cesium iodide CsI2, cesium bromide CsBr2, cesium chloride CsCl2, tin iodide SnI2, tin bromide SnBr2 or tin chloride SnCl2.

5. The method for preparing a perovskite film according to claim 1, wherein: The organic halide is at least one of methylamine iodide FAI, methylamine iodide MAI, methylamine chloride FACl, methylamine chloride MACl, methylamine bromide FABr or methylamine bromide MABr.

6. The method for preparing a perovskite film according to claim 1, wherein: The distance between the electrostatic spraying nozzle and the substrate is 1-50 cm; the voltage of the electrostatic spraying is 20-100 kV; and the electrostatic spraying time is 10-60 seconds.

7. The method for preparing a perovskite film according to claim 2 or 3, characterized in that: The steam chamber is processed in a normal pressure or vacuum state.

8. The method for preparing a perovskite film according to claim 2, characterized in that: The organic halide vapor flows through the steam chamber at a speed of 500-2000 mL / min for a duration of 10-30 min.

9. A perovskite solar cell, comprising a perovskite light absorbing layer, characterized in that: The perovskite light-absorbing layer is a perovskite film prepared by the method for preparing a perovskite film according to any one of claims 1 to 8.

10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cells include formal single-junction perovskite solar cells, inverted single-junction perovskite solar cells, perovskite / perovskite tandem solar cells, perovskite / crystalline silicon tandem solar cells or perovskite / copper indium gallium tin CIGS tandem solar cells.